A user-centered, digitally integrated, and scalable system support climate information generation, use, and exchange within the Central American Integration System (SICA) encompassing 200+ institutions and reaching 180 000 farmers. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
CCAFS scientists have developed a user-centered, digitally integrated, and scalable system to support climate information generation, use, and exchange within the SICA (Central American Integration System), which is co-developed with stakeholders from the regional level through to the mesoscale and local level encompassing 200+ institutions in Central America and reaching ca. 180,000 farmers. This information includes historical climate information, climate forecasts and reports on the likely crop response to the climate for specific conditions in time and space.